Sex differences in cardiometabolic risk factors and in response to lifestyle intervention in prepubertal and pubertal subjects with obesity - Gilardini, Luisa; Croci, Marina; Cavaggioni, Luca; Pasqualinotto, Lucia; Bertoli, Simona (Frontiers in Pediatrics, 2024)
Objectives: Childhood obesity is a growing health problem and requires a tailored treatment. This study explored the sex differences in cardiovascular risk factors in children/adolescent with obesity and in response to a weight loss intervention.Methods: 533 children/adolescents with obesity and their parents underwent to a 3-months lifestyle intervention program. Tanner criteria were used to assess the pubertal stage. Before and after 3 months, anthropometric measurements, blood pressure (BP) and biochemical measurements were assessed.Results: 445 participants completed the treatment (age 12.4±2.7 years, males 45.8%, prepubertal 29.2% , BMI z score 2.3±0.2). In comparison to boys, prepubertal girls had higher values of BMI z score (2.4±02 vs 2.3±0.2, p<0.05), waist circumference z score (2.2±0.3 vs 2.0±0.3, p<0.05), HOMA-IR [2.9(2.1-4.9) vs 2.3(1.5-3.6), p<0.01], prevalence of hypertransaminasemia (41.3% vs 17.7%, p<0.05) and lower levels of HDL cholesterol (46.2±9.8 vs 51.2±10.5 mg/dl, p<0.05). In the pubertal stage, boys had worse cardiometabolic risk profile than girls, including unfavourable measure of systolic BP (z score: 0.6±1.0 vs 0.3±1.0, p<0.01), fasting glucose (87.2±6.1 vs 84.8±7.7 mg/dl, p<0.01), ALT (26.9±21.5 vs 20.2±10.6 U/L, p<0.001) and uric acid (6.1±1.9 vs 5.0±1.0 mg/dl, p<0.001). After the lifestyle intervention, changes in BMI z score (p<0.05) was higher in pubertal boys than pubertal girls. The systolic blood pressure decrease was greater in pubertal boys than in their female counterpart (Δ systolic BP: -7.2 mmHg in boys vs -3.6 mmHg in girls, p<0.05; Δ systolic BP z score: -0.6 in boys vs -0.3 in girls, p<0.05). LDL cholesterol showed an improvement only in boys, ALT in the whole group. Conclusion: Our study showed that a shortterm lifestyle intervention is more effective in reducing BMI z score and cardiovascular risk factors in pubertal boys than in their female counterpart. Further investigation is needed to deepen this gender difference, especially to develop a tailor-made intervention.